(untitled) (Balneo and PRM Research Journal, 2024)
Abstract: Background: Previous studies have demonstrated a direct correlation between pacemaker programming mode and exercise capacity on a long-term follow-up. In the present study we aimed to test whether reprogramming of the pacemaker can produce immediate effects on patients’ exercise capacity. Methods: The exercise capacity of 33 patients wearing dual-chamber pacemakers was evaluated by cardiopulmonary exercise test at 24-hour intervals in two programming modes: initially in the single-chamber ventricular pacing mode with a fixed 60bpm rate, and in the second phase in dual chamber pacing mode with exercise adaptable rate, up to 130bpm. Results: The maximum O2 consumption (VO2 max: 12.82±2.70 mL/kg/min vs 14.52±3.25 mL/kg/min, p=0.02), the O2 consumption at the time of the anaerobic threshold (10.76±2.25 mL/kg/min vs 12.30±2.84 mL/kg/min, p=0.008), the duration of exercise (456.76±116.85 seconds vs 510.57±129.56 seconds, p=0.04) and the maximum workload (84.39±17.89W vs 96.36±24.09W, p=0.01) were significantly lower when the pacemakers were programmed in the single chamber ventricular fixed-rate pacing mode compared to the dual chamber rate adaptive pacing mode. Conclusion: Cardiac pacemaker reprogramming is able to exert immediate effects on exercise capacity. Dual chamber pacing with adaptable rate during physical exercise is superior to single chamber fixed rate pacing.